Exploring a parent-focused physical literacy intervention for early childhood: a pragmatic controlled trial of the PLAYshop - Cassandra Lane; Patti-Jean Naylor; Madison Predy; Mette Kurtzhals; Ryan E. Rhodes; Kayla Morton; Stephen Hunter; Valerie Carson (BMC, 2022)
Abstract Background Parents play a key role in young children's physical activity and physical literacy development. Little research has explored parent-focused interventions to improve young children's physical literacy. We examined if a theory-based, feasible physical literacy training workshop (PLAYshop) for parents could improve their physical literacy knowledge and confidence and improve parenting practices related to facilitating the physical literacy development of their preschool-aged child (3-5 years). The secondary objective was to explore implementation facilitators and barriers. Methods We conducted a pragmatic controlled trial in two Canadian cities (Edmonton and Victoria) from November 2019 - March 2020. A total of 143/151 parents were eligible and assigned to intervention (n = 71) or control group (n = 72). The PLAYshop included: (i) a 75-min in-person workshop with interactive activities and physical literacy educational messages, (ii) educational materials, (iii) an equipment pack, and (iv) two post-workshop booster emails. Surveys measured parents' knowledge and confidence at baseline and follow-up. Application of PLAYshop concepts and implementation facilitators and barriers were explored with interviews of parents and workshop leaders. Repeated measures ANOVAs and thematic analyses were completed. Results Parents' knowledge and confidence improved significantly over time; intervention group changes were significantly greater than control group changes (p < 0.001; ɳ2 = .32). Parents applied PLAYshop concepts at-home, including child-led play, making activities fun, and promoting child manipulative and locomotor skills. Time was a key parental implementation barrier. Program implementation issues varied by context (location and participants). Conclusions PLAYshop participation changed parents' physical literacy knowledge and confidence and physical literacy enhancing play with their children. Implementation feasibility was high. The findings from this real-world trial highlight an efficacious and scalable intervention that warrants further testing. Trial registration ClinicalTrials.gov: NCT04394312 . Registered 19/05/2020.